PENERAPAN RESTORATIVE JUSTICE DALAM PERKARA PERSETUBUHAN TERHADAP ANAK YANG BERAKHIR DENGAN PERKAWINAN - Yasin, Bukhari; Yasir, H. M.; Yulianto, Alfian (Legal Standing : Jurnal Ilmu Hukum, 2024)
This study aims to examine the mechanism of the application of Restorative Justice in resolving criminal cases of sexual intercourse with married children, and to consider the principles of Restorative Justice in court decisions related to the case. The approaches used include legislative and conceptual approaches. The results of the study indicate that the application of Restorative Justice in this case allows for the creation of justice for the victim, with formal requirements in the form of a peace agreement between the parties concerned and the fulfillment of the victim's rights and the perpetrator's responsibilities. Material requirements that must be met include not causing unrest or rejection in society, not triggering social conflict, not threatening national unity, and ensuring that the perpetrator is not a recidivist in accordance with the court's decision.